The girl upstairs - Dwiastuti, Ignati Devy (2016)
‘The Girl Upstairs’ is a 2d animated film about the friendship between a lonely little boy and a reclusive girl. A lonely little boy is left home alone and goes to investigate the reason for his leaky ceiling. He discovers his upstairs neighbour is a girl that lives in a forest where it's constantly raining - and it becomes clear that the source of the rain is the girl's own insecurity. The lonely little boy and the reclusive girl become friends, and through the bond of friendship, manage to make the rainfall stop. This report will discuss the process and challenges encountered in the production of the film.